Audit Expectation Gap between Academics and Auditors in Sri Lanka. - Anojan, V. (Wayamba University of Sri Lanka, 2022)
The primary aim is to find out the audit expectation gap between academics and auditors in Sri Lanka. The four main concepts and applications of the audit were tested in this study. They are the auditor’s responsibilities, audit reliability, key audit matters (KAM) & auditing standards (AS), and usefulness of audited financial statements for decision-making. The population of the study is public university academics in the field of accounting and finance, and independent external auditors in Sri Lanka. The researcher used a developed Likert five-point scale questionnaire to collect data from academics and auditors for the study. The developed questionnaire was distributed among 100 academics and external auditors, and 64 responses were received in this study. Descriptive and inferential analyses were performed in this study. Descriptive statistics confirmed that there is an expectation gap between academics and auditors in Sri Lanka. ANOVA and independent sample test confirmed that there is an expectation gap between academics and students, but there is no significant expectation gap. They have a high level of expectation gap regarding key audit matters and auditing standards application, on the other hand, they have a low level of expectation gap on audited financial statements usage in decision making when compare to standard or expected. There is a high level of expectation gap regarding the key audit matters and auditing standards application between auditors and academics in Sri Lanka, however, there is a low level of expectation gap regarding audit reliability between auditors and academics in Sri Lanka. The results of the study highlight that there is audit expectation between auditors and academics in Sri Lanka. They are the fillers of auditing theories and practices in Sri Lanka, therefore regulatory bodies and accounting professional institutions ought to be taken some effective and efficient actions to create better awareness of auditing and ensure adequate auditing education in Sri Lanka for the sustainability of firms and the economy of the country.
Keywords: Academics; Audit expectation gap; Audit reliability; Auditor’s responsibilities; Independent Auditors; Key audit matters